Immigrant and non-immigrant women: factors that predict leaving an abusive relationship - Amanor-Boadu, Yvonne; Messing, Jill Theresa; Stith, Sandra M.; Anderson, Jared R.; O’Sullivan, Chris; Campbell, Jacquelyn C. (My University, 2012)
This research used logistic regression to test components of Choice & Lamke’s (1997) two-part decision making model and Hamby’s (2008) holistic risk assessment as predictors in the decision to separate from an abusive partner, comparing significant predictors for immigrant (n=497) and non-immigrant (n=808) women. Findings demonstrated that immigrant women reported higher levels of perceived risks/barriers to leaving, and provided some support for the use of a holistic risk assessment in understanding women’s decisions to leave, while also demonstrating that immigrant and non-immigrant women have both similarities and differences in the factors that predict leaving. Clinical and policy implications are addressed.
Keywords: Intimate partner violence; Stay/leave decision; Immigration